1918. Impact of the SARS-CoV-2–Neutralizing Antibody Combination AZD7442 (Tixagevimab/Cilgavimab) on the Severity and Progression of COVID-19 Symptoms in the Phase 3 TACKLE Trial. (15th December 2022) - Campos, Jesus Abraham Simón; Arbetter, Douglas; Montgomery, Hugh; Richard Hobbs, F D; Padilla, Francisco; Kim, Kenneth; Streicher, Katie; Templeton, Alison; Viani, Rolando M; Esser, Mark T
Abstract: Background: Outpatient treatment with SARS-CoV-2–neutralizing antibody combination AZD7442 (tixagevimab/cilgavimab) in adults with mild to moderate COVID-19 significantly reduced progression to severe disease or death through Day 29 and was well-tolerated in the Phase 3 TACKLE study (NCT04723394). We report a post hoc analysis of the impact of AZD7442 in reducing self-reported COVID-19 symptom severity and time to symptom resolution through Day 29 in TACKLE. Methods: In TACKLE, non-hospitalized adults with mild to moderate COVID-19 were randomized 1:1 and dosed ≤7 days from symptom onset with a single 600mg AZD7442 dose (2 consecutive intramuscular (IM) injections, 300 mg of each antibody; n=452) or placebo (n=451). Symptom occurrence and severity were self-reported daily by participants through study Day 29. Participants rated each symptom as not experienced, mild, moderate, severe, or emergency room (ER) or hospital visit. Symptom progression was compared between AZD7442 and placebo using a stratified Cochran-Mantel-Haenszel test. Change from baseline in symptom severity was compared using a mixed model for repeated measures. Time to symptom resolution was compared using Kaplan-Meier and Cox proportional hazards methods. Missing symptom data for those who were hospitalized or died were imputed as either failures or as severity scores of ER or hospital visit. Results: Progression of ≥1 symptoms to a worse severity score occurred in 170 (55.7%) AZD7442- versus 204 (63.4%) placebo-treated participants, translating to a nominally significant relative risk reduction of 12.5% (95% confidence interval 0.5–23.0; P=0.041). Over 29 days, the overall mean improvement from baseline in severity of body aches, chills, cough, diarrhea, fatigue, headache, muscle aches, nausea, and runny nose was significantly greater with AZD7442 versus placebo (Figure). The greatest improvements were observed with cough, fatigue, and muscle aches. Significant differences were observed for most symptoms within 1 and 2 weeks post AZD7442 dosing. Figure. Forest plot for LS difference in severity of COVID-19 symptoms between AZD7442 and placebo through Day 29 CI, confidence interval; LS, least squares. The overall P value is calculated using a mixed model for repeated measures, including terms for symptom severity baseline value, time from symptom onset (≤5 vs >5 days), risk of progression to severe COVID-19 (high vs low), treatment, visit, and treatment by visit interaction. Conclusion: For the treatment of mild to moderate COVID-19, a single IM 600-mg AZD7442 dose was associated with reductions in progression of COVID-19 symptom severity and may hasten symptom improvement through Day 29. Disclosures: Jesus Abraham Simón Campos, MD, AstraZeneca: Board Member|AstraZeneca: Speaker|Eli Lilly: Board Member|Pfizer: Board Member|Roche: Board Member|Roche: Speaker Douglas Arbetter, MPH, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Hugh Montgomery, MD, AstraZeneca: Advisor/Consultant|Millfield Medical Ltd: Advisor/Consultant|UK National Institute for Health Research's Comprehensive Biomedical Research Centre at University College London Hospitals: Grant/Research Support F.D. Richard Hobbs, FMedSci, AstraZeneca: Grant/Research Support|AstraZeneca: Principal investigator|NIHR Applied Research Collaboration, Oxford Thames Valley: Director|Oxford BRC and NIHR MedTech: Investigator|UKRI and NIHR: Grant/Research Support Francisco Padilla, MD, Amgen: Grant/Research Support|Amgen: Personal fees|AstraZeneca: Grant/Research Support|AstraZeneca: Personal fees|Boehringer Ingelheim: Grant/Research Support|Boehringer Ingelheim: Personal fees|Ferrer: Grant/Research Support|Ferrer: Personal fees|Kowa: Grant/Research Support|Kowa: Personal fees|Medix: Grant/Research Support|Medix: Personal fees|Merck Sharp and Dohme: Grant/Research Support|Merck Sharp and Dohme: Personal fees|Novartis: Grant/Research Support|Novartis: Personal fees|Pfizer: Grant/Research Support|Pfizer: Personal fees|Sanofi: Grant/Research Support|Sanofi: Personal fees|Servier: Grant/Research Support|Servier: Personal fees|Silanes: Grant/Research Support|Silanes: Personal fees Kenneth Kim, MD, Adagio: Funding|Eli Lilly: Funding|Merck: Funding|Pfizer: Funding|Regeneron: Speaker|Regeneron: Funding Katie Streicher, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Alison Templeton, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Rolando M. Viani, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Mark T. Esser, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds.